Social psychology of inclusion and exclusion - Abrams, Dominic, 1958-; Hogg, Michael A., 1954-; Marques, José M. (José Mendes) (Psychology Press, 2005)
The book draws together research on individual motivation, small group processes, stigmatization and intergroup relations, to provide a comprehensive social psychological account of social inclusion and exclusion.